(untitled) (Journal of Madenat Alelem, 2022)
The human carries in his body about 1-1.5 kilogram of different microorganisms, which together represent the human microbiota, where everyone has there own microbial environment. This microflora plays a vitally important role and interferes with many of the body’s various physiological, immune, and nutritional functions, which may change according to the variation of many conditions that occur in our life. Probiotics are known as live microorganisms that give positive effects on host health when consumed in sufficient numbers. Probiotics are considered one of the most distinguished safe strategies to restore the vital microbiota which is important to the environment of living organisms in the gastrointestinal tract, as studies have proven its unique ability in the prevention and treatment of many diseases for young and old age people. Probiotics are available commercially in many different formulas and pharmaceutical forms (capsules, pills, tablets, etc.), which may be blamed for many disadvantages, as many complaints were recorded against some international companies producing. This matter encouraged those interested in the food industry field to move towards manufacturing functional foods as therapeutic nutritional products with a high number of live probiotics to achieve the health effect for humans, especially the various dairy products, which are considered one of the best food vehicles to contain and deliver these probiotics, due to their many advantages. This study aimed to highlight the importance of including food with probiotics, specifically dairy products, and preference it on pharmaceutical forms in order to deliver its nutritional and health benefits to humans.